Bodies in Pile: Osteological and Archaeological Analysis of Skeletal Remains from Phaselis Infrastucture - Tolga Karahan; Ahmet İhsan Aytek; Alper Yener Yavuz (Phaselis: Disiplinlerarası Akdeniz Araştırmaları Dergisi)
Phaselis is located within the borders of Tekirova neighborhood of Kemer district. It is an important port city on the Mediterranean trade route. The ongoing excavations in the city reveal important features of the city. One of these excavations is being carried out on the main street connecting the southern harbor of the city with the central harbor where the trade function was intensively carried out. During the 2023 field season in the northern part of the main street, sewage systems were found under the summun dorsum (paving bloks) blocks of the main street of the city. The drainage system starts from the crepis in front of the western wall of the latrina and continues from north to south under the eastern crepidoma (stairs) to the central harbor and ends with a channel through which water flows into the sea. Four skeletons were recovered from the large bath channel during the drainage excavations. All of the individuals are adult males and exhibit similar physical characteristics. The location and morp-hological characteristics of the skeletons, together with the archaeological record, indicate that they cannot be con-sidered as burials. Furthermore, the detailed examination did not reveal any trauma-related lesions, thus ruling out a possible homicide scenario. The strongest hypothesis explanation for the case is that these individuals drowned during a failed escape attempt.